2020
DOI: 10.1073/pnas.1909075117
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insight into the origins and dispersal of the Brazilian coastal natives

Abstract: In the 15th century, ∼900,000 Native Americans, mostly Tupí speakers, lived on the Brazilian coast. By the end of the 18th century, the coastal native populations were declared extinct. The Tupí arrived on the east coast after leaving the Amazonian basin ∼2,000 y before present; however, there is no consensus on how this migration occurred: toward the northern Amazon and then directly to the Atlantic coast, or heading south into the continent and then migrating to the coast. Here we leveraged genomic data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 29 publications
0
38
0
2
Order By: Relevance
“…These demographic differences between Andeans (Quechuans and Aymarans) and other South American indigenous populations have been recurrently corroborated by different studies (Barbieri et al, 2014, 2019; Jota et al, 2011, 2016), and are part of a complex population dynamics in pre‐Columbian times involving fission‐fusion processes (Neel & Salzano, 1967), demographic expansions (Castro e Silva et al, 2020; Ramallo et al, 2013) and differentiation in isolation associated to culture (Hünemeier et al, 2012).…”
Section: The Indigenous Brazilmentioning
confidence: 70%
See 2 more Smart Citations
“…These demographic differences between Andeans (Quechuans and Aymarans) and other South American indigenous populations have been recurrently corroborated by different studies (Barbieri et al, 2014, 2019; Jota et al, 2011, 2016), and are part of a complex population dynamics in pre‐Columbian times involving fission‐fusion processes (Neel & Salzano, 1967), demographic expansions (Castro e Silva et al, 2020; Ramallo et al, 2013) and differentiation in isolation associated to culture (Hünemeier et al, 2012).…”
Section: The Indigenous Brazilmentioning
confidence: 70%
“…Tarazona-Santos et al (2001) suggested that cultural differences like farming and the complex hierarchy of the Andean civilization should have driven a larger gene flow between populations located even 4,000 km apart, while this contact was more restrict in other landscapes, like Amazonia. These demographic differences between Andeans (Quechuans and Aymarans) and other South American indigenous populations have been recurrently corroborated by different studies (Barbieri et al, 2014(Barbieri et al, , 2019Jota et al, 2011Jota et al, , 2016, and are part of a complex population dynamics in pre-Columbian times involving fission-fusion processes (Neel & Salzano, 1967), demographic expansions (Castro e Silva et al, 2020;Ramallo et al, 2013) and differentiation in isolation associated to culture (Hünemeier et al, 2012).…”
Section: The Indigenous Brazilmentioning
confidence: 78%
See 1 more Smart Citation
“…With a ; yellow, Epigen-Brazil initiative; 28 gray, Baependi Heart Study; 29 red, Native American/ Tupí-Guarani. 30 limited budget available in resourcelimited settings, it would also be highly recommended that in parallel with the genomes that are sequenced, the rest of the interested participants could be genotyped by high-definition microarrays that would allow researchers to evaluate the common genomic structure, to create selected pharmacogenomics data, and to model disease polygenic scores. This genomic information can be readily applicable in primary care and first line interventions, such as in screening programs.…”
Section: Sketching a Roadmapmentioning
confidence: 99%
“…Geographic Distribution of Some of the Ongoing Cohort Studies within BrazilColored circles indicate states where cohorts of Brazilians are followed in the different studies. Blue, ELSA-Brazil;26 green, Brazilian Longitudinal Study of Aging (ELSI-Brazil 27 ); yellow, Epigen-Brazil initiative;28 gray, Baependi Heart Study;29 red, Native American/ Tupí-Guarani 30.…”
mentioning
confidence: 99%